Magnetic field dependence of singlet fission in solutions of diphenyl tetracene - Thompson, Nicholas J. (Philos Trans A Math Phys Eng Sci, 2015)
Magnetic field effects provide a convenient and specific probe of singlet exciton fission within optoelectronic devices. Here, we demonstrate that this tool may also be applied to screen potential fission material candidates in solution. We characterize the phenomenon in diphenyl tetracene (DPT), which shows strong fluorescence modulation and the expected field dependence in its transient decay as a function of concentration. Solution measurements may also be used to test for the presence of an intermediate charge transfer state, but we observe no changes to the field dependence of DPT singlet exciton fission in toluene relative to chloroform.